2013
DOI: 10.1007/s10488-013-0492-6
|View full text |Cite
|
Sign up to set email alerts
|

National Trainers’ Perspectives on Challenges to Implementation of an Empirically-Supported Mental Health Treatment

Abstract: This study examined perceived challenges to implementation of an empirically supported mental health treatment for youth (Trauma-Focused Cognitive Behavioral Therapy; TF-CBT) and explored the potential use of technology-based resources in treatment delivery. Thematic interviews were conducted with 19 approved national TF-CBT trainers to assess their perspectives about challenges to implementation of TF-CBT and to explore their perceptions about the potential value of innovative, technology-based solutions to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…The authors then met in a consensus conference to discuss the categories, resolve questions, and refine the thematic categories prior to developing the final thematic categories (Table 1). Recent projects evaluating pilot data and focus group feedback for adapting interventions have used similar analytic approaches to qualitative research (e.g., Davidson, de Arellano, and Ruggiero 2012; Grubaugh et al in press; Hanson et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…The authors then met in a consensus conference to discuss the categories, resolve questions, and refine the thematic categories prior to developing the final thematic categories (Table 1). Recent projects evaluating pilot data and focus group feedback for adapting interventions have used similar analytic approaches to qualitative research (e.g., Davidson, de Arellano, and Ruggiero 2012; Grubaugh et al in press; Hanson et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously as the referral network of behavioral health providers was built during the preparation phase, the PACTS team also began to provide training, consultation, and technical assistance to behavioral health and non-behavioral health staff in TF-CBT (see Figure 1 for a visual depiction of described activities; Hanson et al, 2014; Powell et al, 2012). Since 2011, six cohorts (182 therapists and 34 supervisors) have received training in TF-CBT.…”
Section: Case Study: Creating a Trauma-informed Behavioral Health Sysmentioning
confidence: 99%
“…Thus, for research on implementation, we would ultimately seek to develop cost-effective and accurate fidelity monitoring systems that can easily be embedded within the available community or service systems. Hanson et al (2013) found that implementation interventionists recognize the difficulty in maintaining fidelity and acknowledge the high resource intensity of effective intervention implementation, leading them to advocate for the increased use of technology to monitor and reduce drift. In addition to accurate fidelity monitoring, usability requires that we would have a minimum time lag between fidelity rating and feedback to the facilitator.…”
Section: Introductionmentioning
confidence: 99%